Enhancing Midwifery Students’ Knowledge and Skills Through Augmented Reality Learning Media - Erniati, Erniati; Ahmad, Mardiana; Syafruddin, Syafruddin; Idrus, Hasta Handayani (Journal of Neonatal Surgery, 2025)
Objective: Improving the Knowledge and Skills of Midwifery Students through Augmented Reality-Based Learning Method: This research method is a literature review approach that is taken based on national and international scientific journals related to the use of Augmented Reality Technology in improving midwifery student skills. Retrieval of literature reviews sorted from several databases, namely Pub Med, , Sci lit Science-direct, Google Scholar, and Semantic Scholar databases published between 2018-2024. This review was compiled through searching scientific articles with the keywords 'Learning, Skills, Knowledge, Augmented Reality, Midwifery Students'. After filtering for publication years 2018-2024, 110 articles were found. 52 articles were selected based on abstract, full text, open access, and duplication. Then the final process the author reads and sorts the articles. Based on the criteria set, 30 relevant articles were obtained. Results: Augmented Reality learning media makes learning more interactive and interesting so that students can access additional information, 3D visualizations, or live simulations that increase understanding and retention of information. Conclusion: The application of Augmented Reality (AR) technology has a positive effect on students by combining digital elements with the real world so as to increase student knowledge and skills.